Dampak Pembelajaran Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa di STAIN Majene - Putra, Nur Astaman; Atirah, Atirah (Politeknik Negeri FakFak, 2025)
Entrepreneurship has become a crucial pillar in economic development, particularly in addressing the challenges posed by globalization and the Fourth Industrial Revolution (Industry 4.0). This study aims to quantitatively describe the impact of entrepreneurship education on students' entrepreneurial interest. Sampling was conducted using a purposive sampling method, selected based on the researchers’ considerations. The reason for this sampling technique was that the selected classes had completed the entrepreneurship course. Total sampling was used, resulting in a sample of 121 students from four selected classes. The research instrument was an online questionnaire distributed to the students, and the collected data were analyzed using regression analysis to evaluate students’ perceptions of entrepreneurship education. The results of the study indicate that entrepreneurship education has a “positive” impact on students' entrepreneurial interest, as represented by indicators such as self-confidence, creative and innovative thinking, future orientation, as well as the enhancement of honesty and independence values among students.